Using The Wisdom of Wisdomers in Eliminating Teenager Offenses - Кhoyilova Mekhriniso Djuraevna (Genius Journals, 2021)
This article deals with the issues of family relations, as well as the issues of raising a harmoniously developed generation through a healthy lifestyle, health protection, which are mentioned in the text of the sacred book of our ancestors Zoroastrians Avesto
Keywords: Heritage; “Avesto”; health; family